2022
DOI: 10.3389/fsurg.2022.842776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine-Assisted Intravenous Anesthesia on Gastrointestinal Motility in Colon Cancer Patients After Open Colectomy

Abstract: BackgroundTo explore the effect of dexmedetomidine (Dex)-assisted intravenous anesthesia on gastrointestinal motility in patients with colon cancer (CC) after open colectomy.MethodsA total of 102 patients with CC, undergoing open colectomy in our hospital from January 2018 to January 2020, were selected and randomly divided into an observation group (n = 51) and a control group (n = 51). The patients in the control group received a routine combination of intravenous and inhalation anesthesia (CIIA), while thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In animal studies, DEX has shown to have a dose-dependent effect on the inhibition of gastrointestinal motility (duodenum, jejunum, colon and cecum) in donkeys [26]. However, the effects on the lower gastrointestinal tract in humans suggest that DEX may have a positive effect on improving return of motility following abdominal surgery in adult patients [27]. Results of animal experiments have suggested that α-adrenoceptor mediated pathways may play a role in modulating smooth muscle motility, but mixed effects have been reported [15,17,25,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, DEX has shown to have a dose-dependent effect on the inhibition of gastrointestinal motility (duodenum, jejunum, colon and cecum) in donkeys [26]. However, the effects on the lower gastrointestinal tract in humans suggest that DEX may have a positive effect on improving return of motility following abdominal surgery in adult patients [27]. Results of animal experiments have suggested that α-adrenoceptor mediated pathways may play a role in modulating smooth muscle motility, but mixed effects have been reported [15,17,25,28,29].…”
Section: Discussionmentioning
confidence: 99%